USING MINDFULNESS, AS THE METHOD OF SELF-REGULATION FOR CREATIVITY DEVELOPMENT - Gevorgyan , A. Kh. (Modern Psychology, 2021)
The objective of the study is to find out the influence of the mindfulness meditation on the development of creativity. The article describes how the mindfulness meditation can promote the development of creativity. Survey, correlational and experimental research was done using the research methods of testing and experiment. The methods of diagnostics are the test by F. Williams for creativity assessment and Five Facet Mindfulness Questionnaire (FFMQ) by Ruth Baer. The correlational research showed that there were considerable connections among the level of awareness and creativity. As a result of the qualitative analyses of the experiment, it turned out that the solutions suggested by the students were more creative after the meditations. The results of the retesting showed that the level of the creativity has improved after the 5-days mindfulness training. The study opens new perspectives to manipulate with the mindfulness based interventions in order to receive more significant results for creativity development.
Keywords: mindfulness, meditation, creativity, self-regulation, training, development.